KEMAMPUAN KERJA, EFIKASI, BUDAYA, KARAKTERISTIK PEKERJAAN DAN KEPUASAN KERJA KARYAWAN (Value : Jurnal Manajemen dan Akuntansi, 2022)
PT Bio Takara Purwokerto in running its business strives to create and manage employee job satisfaction well, but there are various factors that affect employee job satisfaction such as work ability, self-efficacy, organizational culture, and job characteristics. This research aims to determine the effect of work ability, self-efficacy, organizational culture, and job characteristics on employee job satisfaction at PT Bio Takara Purwokerto. This research used Multiple Linear Regression Analysis, and data were obtained from questionnaires which were distributed directly to the respondents. The results of this research indicate that work ability, self-efficacy, organizational culture, and job characteristics have a significant positive effect on employee job satisfaction at PT Bio Takara Purwokerto.Keywords: Work Ability, Self-Efficacy, Organizational Culture, Job Characteristics, and Employee Job Satisfactio